Determine The Risk Of Long-Term Complications In Patients With Acute Coronary Syndrome - M.X., Maksudova; G.R, Qodirova; A.Sh, Nadzhmiddinov (PT. Antis International Publisher, 2024)
The article is devoted to one of the current topics of modern healthcare - acute coronary syndrome (ACS). Most patients had associated and comorbid diseases, primarily such as stable angina, chronic heart failure, broncho-obstructive diseases and diabetes mellitus, which in some cases required treatment adjustments [1]. The article provides information on the etiology of acute coronary syndrome, clinical symptoms and risk factors that may develop in patients.